Porphyrin‐adsorbed Allograft Bone: A Photoactive, Antibiofilm Surface. Issue 9 (September 2015) - Dastgheyb, Sana S.; Toorkey, Cyrus B.; Shapiro, Irving M.; Hickok, Noreen J.
Abstract: Background: Allograft bone is commonly used to augment bone stock. Unfortunately, allograft is prone to bacterial contamination and current antimicrobial therapies are inadequate. Photoactivated porphyrins combat bacterial growth by production of reactive oxygen species (ROS); however, to our knowledge, they have not been tested in the setting of allograft bone. Questions/purposes: We asked: (1) Does 5, 10, 15, 20‐tetrakis‐(4‐aminophenyl)‐porphyrin (TAPP) stably adsorb to morselized, mineralized allograft? (2) Does Staphylococcus aureus acquire TAPP from TAPP‐allograft? (3) Is TAPP‐allograft antibacterial to S. aureus ? (4) Is ROS production critical for antimicrobial activity? (5) Does illuminated TAPP‐allograft dislodge biofilm? (6) Could other photoactive dyes (TAPP, TMPyP, TSP, THP, and methylene blue) confer antimicrobial properties to allograft? Methods: TAPP adsorption to allograft (TAPP‐allograft), its localization in S. aureus, and TAPP‐allograft long‐term stability were determined spectrophotometrically. Antimicrobial activity was measured while activated with light or in the dark during incubation with S. aureus or after allograft biofilm formation. Glutathione was added to illuminated TAPP‐allograft to quench ROS and antimicrobial activity was determined. Light‐dependent antimicrobial activity of other photoactive dyes (TMPyP, TSP, THP, and methylene blue) adsorbed to allograft was also tested. Results: We found (1) porphyrins strongly adhere to bone allograft; and (2) the bacteria are not able to sequester TAPP from the TAPP‐allograft; (3) when illuminated, TAPP‐allograft is resistant to bacterial adherence; (4) the effects of TAPP are inhibited by the radical scavenger glutathione, indicating ROS‐dependent antimicrobial activity; (5) illumination of TAPP‐allograft disrupts biofilms; and, (6) other photoactive dyes impede biofilm formation on allograft bone in the presence of light. Conclusions: Porphyrins stably associate with allograft and are inactive until illuminated. Illuminated TAPP‐allograft markedly reduces bacterial colonization, which is restored in the presence of radical scavengers. Finally, illuminated TAPP‐allograft disrupts biofilms. Clinical Relevance: The findings of this in vitro study suggest that loading bone allograft with biocompatible porphyrins before surgery might allow increased sterility of the allograft during implantation. Future testing in an animal model will determine if these in vitro activities can be used to prevent allograft‐based infection in an establishing osteomyelitis.